2012
DOI: 10.1523/jneurosci.1316-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

MeCP2 Is Critical for Maintaining Mature Neuronal Networks and Global Brain Anatomy during Late Stages of Postnatal Brain Development and in the Mature Adult Brain

Abstract: Mutations in the X-linked gene, methyl-CpG binding protein 2 (Mecp2), underlie a wide range of neuropsychiatric disorders, most commonly, Rett Syndrome (RTT), a severe autism spectrum disorder that affects about one in 10,000 female live births. Because mutations in the Mecp2 gene occur in the germ cells with onset of neurological symptoms occurring in early childhood, the role of MeCP2 has been ascribed to brain maturation at a specific developmental window. Here, we show similar kinetics of onset and progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
155
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(179 citation statements)
references
References 31 publications
21
155
1
2
Order By: Relevance
“…IGF1 treatment abolishes this plasticity and stabilizes the underlying circuits and synapsespossibly via effects on inhibitory systems in the cortex (51) or on homeostatic mechanisms (52). The effect on functional circuits in the adult visual cortex reflects the emerging consensus that the consequences of MeCP2 loss are felt throughout life (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…IGF1 treatment abolishes this plasticity and stabilizes the underlying circuits and synapsespossibly via effects on inhibitory systems in the cortex (51) or on homeostatic mechanisms (52). The effect on functional circuits in the adult visual cortex reflects the emerging consensus that the consequences of MeCP2 loss are felt throughout life (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, considering the delay in the phenotypic onset of RTT caused by germline Mecp2 mutations and the pattern of MeCP2 expression, it is of great value to explore the function of MeCP2 in the postnatal brain. It has been shown that deletion of MeCP2 after birth produces phenotypes comparable to those in Mecp2-null mice and disturbs mature neuronal networks as well as the expression of synaptic proteins [24,25]. These findings indicate the requirement of MeCP2 to maintain brain functions in the postnatal period.…”
Section: Introductionmentioning
confidence: 95%
“…These findings argue that the levels of MeCP2 must be tightly regulated to ensure normal neurological function. Importantly, it is increasingly clear that maintenance of MeCP2 levels throughout life is critical, as revealed by recent reports demonstrating that inducible adult knockout of Mecp2 recapitulated the germline-null phenotypes (McGraw et al 2011;Cheval et al 2012;Nguyen et al 2012). In human brains, MeCP2 protein level is repressed during the fetal stages and elevated during postnatal development (Balmer et al 2003), which could be critical for the timely regulation of expression of hundreds of downstream genes (Chahrour et al 2008).…”
mentioning
confidence: 99%